Respuesta :

sgo

Answer:

118

Step-by-step explanation:

[tex]10^{2} + 2(6-3)^{2}[/tex]   To start off, we work in the Parenthesis; 6-3 = 3

[tex]10^{2} + 2(3)^{2}[/tex]  Now, we must do the exponents; 10^2 = 100; 3^2 = 9

[tex]100 + 2(9)[/tex]   Next, we have to distribute the 2 to the 9; 2 x 9 = 18

[tex]100 + 18[/tex]  Lastly, we have to add 100 and 18; 100 + 18 = 118

So! Our final answer is 118!

Hope this Helps! :)

Have any questions? Ask below in the comments and I will try my best to answer.

-SGO

Answer:

118

Step-by-step explanation:

m)  [tex]10^{2} + 2(6-3)^{2} = 10^{2} + 2(3)^{2} = 10^{2} + 2(9)= 100 + 18 = 118[/tex]